Anaerobic digestion of vinasse from sugarcane ethanol production in Brazil: Challenges and perspectives. (April 2015) - Moraes, Bruna S.; Zaiat, Marcelo; Bonomi, Antonio
Abstract: The replacement of fossil fuels by biofuels has been extremely important worldwide to stimulate the growth of economies based on the sustainability through the use of renewable resources. Anaerobic digestion for biogas production is recognized as a clean technology that allies the suitability of wastes with energy generation, fulfilling the requirements for a sustainable alternative to provide the optimization of the biofuels production. This alternative is especially interesting for the sugarcane ethanol production in Brazil, in which the generation of vinasse, the main liquid waste, is very expressive. Nevertheless, the use of vinasse for anaerobic digestion has been finding some challenges to its establishment in the Brazilian sugarcane biorefineries. This paper reviews the actual context of anaerobic digestion within the sugarcane ethanol production in Brazil, presenting the main obstacles for its full application and the directions to promote it as well. Alternatives for biogas use are also presented and compared, highlighting the environmental and energy advantages of applying anaerobic digestion in the sugarcane biorefineries. This scenario is envisaged as a suitable way to achieve the future biorefineries model, based on the use and recovery of renewable resources with economic, social, and environmental benefits.